STUDI KOMPARASI HASIL BELAJAR SOSIOLOGI ANTARA SISWA SMA N 1 SURAKARTA DAN SMA N 3 SURAKARTA JURUSAN IPS KELAS XI YANG MENGIKUTI BIMBINGAN BELAJAR DI GANESHA OPERATION, NEUTRON, DAN PRIMAGAMA TAHUN PELAJARAN 2012/2013 - Eka. P., Niken Septiana (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
Abstract. Niken Septiana Eka. P. K8409042. STUDY RESULTS COMPARISON BETWEEN SOCIOLOGY STUDENT LEARNING SMA N SMA N 1 SURAKARTA AND 3 CLASS XI IPS SURAKARTA DEPARTMENT OF THE FOLLOWING LEARNING MENTORING IN GANESHA OPERATION, NEUTRON, AND PRIMAGAMA FOR ACADEMICAL YEAR OF 2013/2014. Thesis, Surakarta: Teacher Training and Education Faculty. Sebelas Maret University of Surakarta. Juny. 2013. The aims of the research are to find: (1) differences in learning outcomes between students 'social studies sociology class XI SMA N 1 Surakarta and IPS students in class XI SMA N 3 Surakarta, (2) differences in students' learning outcomes sociology class XI IPS SMA N 1 Surakarta and IPS students class XI SMA N 3 Surakarta who follow tutoring Ganesha Operation, Neutron, and Primagama, (3) the place of origin and school tutoring affect the average student learning outcomes sociology class XI IPS SMA N 1 Surakarta and IPS students of class XI SMA N 3 Surakarta, (4) how much influence the differences and variations in the place of origin school tutoring to the average student learning outcomes sociology class XI IPS SMA N 1 Surakarta and students of class XI IPS SMA N 3 Surakarta. This research included in Ex-postfacto with quantitative approach. The study population was all students majoring in social studies class XI SMA Negeri 1 Surakarta and all students majoring in social studies class XI SMA Negeri 3 Surakarta. Samples were students majoring in social studies class XI students of SMA Negeri 1 Surakarta and students majoring in social studies class XI SMA Negeri 3 Surakarta who follow the guidance of learning outside of school (Ganesha Operation, Neutron, and Primagama) as many as 50 students. Sampling technique using multistage cluster random sampling technique. Data collection techniques using tests and school documents. Hypothesis testing using t-test and t-test multiple comparison Scheffe. Based on the results of this study concluded: the first hypothesis